Micronuclear DNA sequences of Oxytricha fallax homologous to the macronuclear inverted terminal repeat. - Dawson, D (1982)
The macronucleus of the protozoan Oxytricha fallax is generated from a micronucleus following conjugation. While the micronucleus contains high molecular weight DNA, the macronucleus contains only short linear DNA molecules which all end in the same 20 bp inverted terminal repeat (Ma-ITR). The Ma-ITR was radioactively labeled and purified for use as a probe in hybridizations to micronuclear and macronuclear DNA. Sequences homologous to the Ma-ITR were detected in micronuclear DNA. The copy number of the repeat in the micronuclear genome is approximately that required to encode the macronuclear DNA termini. The micronuclear copies are found embedded in repeated long sequence blocks.